Rekomendasi Pemupukan K Spesifik Lokasi Untuk Tanaman Padi Sawah - Adnyana, I Made (Universitas Muhammadiyah Yogyakarta, 2014)
The efficiency of fertilizer use is changing greatly depending on soil properties, fertilizer type, irrigation and level of intensive cultivation. A site specific potassium (K) experiment was conducted to formulate the fertilizer recommendation of K for rice plant in different K soil status. The objective of this research were to select a proper soil test method, classify the soil test value of K into two or more classes and fertilizer recommendation of K to rice plant. The result showed that the method of NH4OAc 1 N pH 7 was the best technique for soil analysis. Based on the method, there are 3 available classes of K i.e. low, medium and high. The soil with the highest availability of K does not require fertilizing with K, because it has been fulfilled by the water irrigation and straw. The fertilizer recommendation of K for rice plant at medium class is less than low class.